The Description of Students' Career Adaptability in Senior High School - Rahmansyah, Faisal Akbar; Supriatna, Mamat; Budiamin, Amin (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
This study aims to know the description of students' career adaptability. A quantitative approach is used in this study, using Survey Research Designs. The sampling technique is cluster random sampling. The subject of this research involved 565 students at SMAN 1 Lemahabang Cirebon for grades X, XI, and XII. Data collection was carried out using a career adaptability scale. The career adaptability scale was adapted from the Career Adapt-Abilities Scale (CAAS) measurement by Savickas (2012) which has been translated into Indonesian by Rahayu (2021). Data processing uses the Rasch model approach. The results of the study shows that high school students' career adaptability is in the medium category with a presentation of 73.4 percent. The results of the additional analysis show that there are differences in the distribution of career adaptability levels of students for each level.